(untitled) (World Bulletin of Public Health, 2025)
Esophageal and gastric varicosity in children is a serious medical problem associated with a high risk of life-threatening bleeding. Despite the achieved successes in diagnostics and treatment of this pathology, the frequency of complications remains high, which determines the relevance of further improvement of therapeutic and diagnostic approaches. The development of optimal algorithms for management of pediatric patients taking into account anatomo-physiological features of the growing organism is of particular importance. Timely diagnosis and choice of optimal treatment tactics play a key role in prevention and treatment of bleeding from esophageal and gastric varices in children. In this connection it is urgent to improve existing and develop new methods of diagnostics and treatment of this pathology in pediatric patients.